Improving pain‐related communication in children with autism spectrum disorder and intellectual disability - Rachel Fitzpatrick; Brian E. McGuire; Helena K. Lydon (Wiley, 2022)
Abstract The communication of pain in individuals with co‐morbid Autism Spectrum Disorder and intellectual disability (ASD‐ID) is largely unexplored. The communication deficits associated with ASD‐ID can result in nonverbal behavior such as self‐injurious behavior, aggression, irritability, and reduced activity as a means to communicate that pain is present. The objective of this study was to determine whether a behavioral‐based educational intervention could increase the pain‐related communication of children with ASD‐ID who experience pain frequently. Specifically, the study aimed to determine if children with ASD‐ID can label the location of their pain or quantify pain severity and request pain relief. The sample included three children with ASD‐ID who experienced pain frequently. The intervention utilized educational materials and behavioral reinforcements and the intervention was conducted using a series of case studies. Pain was assessed daily by caregivers using the Non‐Communicating Children's Pain Checklist-Postoperative (NCCPC‐PV) and the ability of the individual to identify and express pain was recorded using the Wong Baker FACES Pain (WBFPS) Scale. Challenging behavior was recorded based on frequency count. The results indicated that all participants displayed the ability to independently respond to a question about how they were feeling by vocalizing the location of pain or indicating their level of pain on the WBFPS and requesting pain relief. The results suggest a role for behavioral‐based educational interventions to promote communication of pain in people with ASD‐ID.